The Oxford Handbook of Tourism History 2022
DOI: 10.1093/oxfordhb/9780190889555.013.35
|View full text |Cite
|
Sign up to set email alerts
|

Culinary Tourism

Abstract: Culinary tourism, also known as food tourism and gastronomic tourism, is simultaneously a scholarly field of inquiry, a niche within the tourism industry, and a human impulse to “eat out of curiosity” and try new food experiences. Two key themes emerge in the current scholarship around food and travel: developing critical frameworks for a cohesive discipline and connecting both the practice and study of culinary tourism to sustainability in the broadest sense of the word to ensure that these projects benefit u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 0 publications
0
17
0
7
Order By: Relevance
“…This is key because use of specific culinary traditions of given communities is usually seen as a sign of authenticity (Giampiccoli et al, 2020) which contributes to a positive visitor experience. Thus, participating in the food preparation process has the potential to arouse the visitors' feelings through the attractive presentation, aroma, taste, sight and smell of the traditional food (Long, 2004). This experience has a powerful ability to connect visitors and the local people (Bessiere and Tibere, 2013;Hillel et al, 2013), and to create beautiful visitor experiences (Bjork and Kauppinen-Raisanen, 2014) which in turn create strong community benefits (Giampiccoli et al, 2020) and a sense of pride in the destination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is key because use of specific culinary traditions of given communities is usually seen as a sign of authenticity (Giampiccoli et al, 2020) which contributes to a positive visitor experience. Thus, participating in the food preparation process has the potential to arouse the visitors' feelings through the attractive presentation, aroma, taste, sight and smell of the traditional food (Long, 2004). This experience has a powerful ability to connect visitors and the local people (Bessiere and Tibere, 2013;Hillel et al, 2013), and to create beautiful visitor experiences (Bjork and Kauppinen-Raisanen, 2014) which in turn create strong community benefits (Giampiccoli et al, 2020) and a sense of pride in the destination.…”
Section: Discussionmentioning
confidence: 99%
“…These experiences arouse the visitors' feelings as they connect a destination's history, culture, landscapes and the people (Bessiere and Tibere, 2013;Hillel et al, 2013;Sims, 2009). These social connections are built through the attractive presentation, aroma, taste, sight and smell of the traditional food (Long, 2004) as well as the associated explanations of the methods for growing the foods, preparing it, the norms and values associated with the whole process. In this sense, eating traditional food takes the visitor off into unknown culinary realms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A growing number of tourists seek authenticity through tourism dining (Hjalager & Richards, 2002;Le et al, 2019;Quan & Wang, 2004); they value it as a crucial part in understanding local cultures during holidays (Falconer, 2013). Unlike other forms of travel activities, consumption and enjoyment of local cuisines as a source of embodied experience, meaning and pleasure (Hjalager & Richards, 2002) have become a way of experiencing other cultures and appreciating the socio-cultural characteristics of a destination (Long, 2004). Previous studies have reported an intricate relationship between food and tourism.…”
Section: Introductionmentioning
confidence: 99%
“…The presentation of heritage food dishes reveals the particular culture determining its authenticity (Nield et al, 2000). Each nation has its unique gastronomical tradition, which comprises the selection of food, presentation of dishes, preparation skills, and the aesthetics of each dish (Long, 2004). Furthermore, Bessière (2013) stated that adopting table manners are a step towards understanding the cultures, tastes and all the good things the region has to offer in consuming gastronomic specialities.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Unfamiliarity with presentation and table manners (Bessière, 2013;Long, 2004;Nield et al, 2000). • Most of the chefs agreed that the presentation of the dish is important for authenticity because it is reflected in the culture of the country (IT/SA).…”
mentioning
confidence: 99%